TORRE LLAUDER, FIGLINA AMPHORALIS - Prevosti Monclús, Marta; Clariana Roig, Joan Francesc (Rei Cretariae Romanae Fautorum Acta, 2024)
The Torre Llauder pottery workshop, where evidence was found of the manufacture of Pascual 1 and Dressel 2–4 amphoras in the 1960s and 70s, is one of the most emblematic of the Laietania region. Marià Ribas had already expressed her opinion that tegulae with the L·HER·OPT stamp had also been manufactured there. In addition, it was theorised that this pottery had also produced plain ware. In this paper we present the results of the analysis of samples of the above mentioned types of pottery, carried out with the aim of shedding some light on these questions.